Internalization of Religious Morality in the Implementation of Congregational Dhuhr Prayer Among Students at State Islamic Madrasah Tsanawiyah Negeri 2 Muaro Jambi - Ningrum Wiyanti; Yudi Kurniawan (Lembaga Bale Literasi, 2025)
Religious moral character formation remains a central challenge in Islamic education, particularly in cultivating students' worship discipline within the madrasah environment. This study investigates the internalization of religious morality (akhlak religius) through congregational Dhuhr prayer at State Islamic Madrasah Tsanawiyah Negeri 2 Muaro Jambi, focusing on the internalization process, observable forms of student discipline, and the factors that support and hinder the process. A qualitative field research design was employed, with data collected through observation, semi-structured interviews, and documentation involving the school principal, Aqidah Akhlak teacher, homeroom teachers, and students selected through purposive sampling. Data were analyzed using the Miles, Huberman, and Saldana model and validated through source, technique, and time triangulation. The findings demonstrate that internalization unfolds through three progressive stages: value transformation, value transaction, and value trans-internalization. Observable manifestations include timeliness in prayer attendance, orderliness and reverence during worship, personal accountability toward worship obligations, and compliance with the madrasah's religious norms. Teacher exemplary conduct and active participation emerged as the most decisive supporting factor, alongside strong institutional commitment and peer social accountability. The primary hindering factors were inconsistent home-based religious reinforcement, competing social attractions during the prayer period, and individual variations in students' spiritual readiness. The study concludes that congregational Dhuhr prayer, when embedded within a structured and consistent institutional framework, constitutes a powerful medium for authentic religious moral character formation among junior high school students.